Effects of a prosocial behavior program in university students - Arias Gallegos, Walter L. (2021)
The aim of this study was to evaluate the effectiveness of a prosocial behavior program in a group of university students from a private university in Arequipa. The intentional sample consisted of 26 students with behaviors that violate rules. They were divided into two groups (experimental and control) and they were administered the Attitudes Towards the Practice of Moral Values test. The research was quasi-experimental and pre and post-test measurements were made before and after the application of the program. The results indicate that there were not significant differences between the experimental group and the control group, although there were significant differences between pre-test and post-test conditions.